Effect of tetrahydroaminoacridine on cognition, function and behaviour in Alzheimer's disease. - Molloy, D W (1991)
OBJECTIVE: To determine the efficacy of tetrahydroaminoacridine (THA) in Alzheimer's disease. DESIGN: Randomized, double-blind, multiple crossover trial with three treatment periods, each consisting of 3 weeks of active drug therapy and 3 weeks of placebo administration. SETTING: Referral-based geriatric practice in a community hospital. PATIENTS: Thirty-four patients with moderate to severe Alzheimer's disease. Subjects were included if they had stage 3 to 6 disease (as determined by the Reisberg scale) and had not been taking psychotropic drugs for at least 1 month and if informed consent had been obtained from the patients and their next of kin. INTERVENTIONS: Fifty to 100 mg of THA daily and matched placebo. RESULTS: Of the initial 34 patients 14 experienced liver toxicity and 3 gastrointestinal side effects during the study; however, all 22 who completed the study were able to tolerate at least the minimum dose. For the 22 patients there was no clinically or statistically significant effect of THA on cognition, functional status or behaviour. The results for individual patients showed no subgroup of THA-responsive patients. CONCLUSION: THA has no clinically important benefits in Alzheimer's disease and is associated with appreciable toxic effects.